Experiences of camouflaging by AFAB University students with ADHD in South Africa - Prinsloo, Estelle (Department of Psychology, 2025)
Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder that continues to be underdiagnosed in people assigned female at birth (AFAB). Increasingly, the gender disparity in ADHD prevalence rates is attributed to differences in the disorder's presentation. A factor that is yet to be explored is the role that camouflaging, or acting neurotypically, plays in the presentation of ADHD in AFAB people. Camouflaging, which has mainly been studied in relation to autism, refers to cognitive and behavioural adaptations that assist neurodiverse people to cope cognitively and socially. This study aimed to investigate camouflaging from the perspective of AFAB university students with ADHD. University students were chosen as the study's sample population as few studies on ADHD focus on this population group. By using an interpretive phenomenological analysis (IPA) approach, the study explored the experiences of camouflaging by 12 AFAB university students with ADHD. The study also sought to gain insight into the camouflaging strategies that participants recognise themselves using and under what circumstances. Three group experiential themes (GETs) were identified in the data, namely Experiences of Living with ADHD, Experiences of Camouflaging, and Camouflaging Strategies. The themes provide important context for participants' need to camouflage and describe their experiences and perceptions of acting neurotypically. Furthermore, the data show that participants employ camouflaging strategies similar to those used by autistic people as well as strategies that speak to challenges more specific to ADHD. By exploring how AFAB university students with ADHD navigate and adapt to neurotypical standards and expectations, the study contributes to a growing understanding of how the disorder manifests in AFAB people and to ADHD research in South Africa.